Application of the ecosystem functions framework to community woodlands - Agbenyega, Olivia (Cranfield University, 2007)
The UK government provides financial incentives to land owners who promote community use of newly-planted woodlands. De Groot et al. (2002) have developed a framework for classifying ecosystem functions. This research applies this framework to identify and describe perceptions of the function, use and value of community woodlands in order to inform local management and government policy. The research was an exploratory and descriptive case study with an initial flexible and final fixed stage. A poplar wood (Pegnut Wood) and two mixed-broadleaf woodlands(Clapham Park Wood and Reynolds Wood), all planted in Bedfordshire between 1993 and 1998, provided the case studies. Data collection methods included semi-structured interviews, self-administered structured questionnaires, direct observation, modelling of tree data and review of secondary documents. In total 172 out of 400 local residents, 20 on-site visitors, and 8 other stakeholders (owners, government institutions and conservation groups) gave responses. The primary motivations of the owners for establishing the woods were production, information and habitat functions. However financial cost-benefit analyses indicated negative returns to owners without government grants. In the first set of interviews 43- 58% of the local respondents at each site described the selected woods and community woods as “very important”. There was a significant positive association between nearness to the woods and level of importance. Those who visited the woods placed greatest emphasis on the use of the woods for exercise and recreation (48-64%), and as a wildlife habitat (50-52%). Using the ecosystem function framework, local respondents at Pegnut Wood and Clapham Park Wood placed greatest value on habitat (29-39%) and information functions (33-38%) and lowest value on regulation (14-19%), production (5-8%) and negative functions (7-8%). Respondents at Reynolds Wood placed the greatest relative importance on negative functions (36%). Across the three sites, local respondents placed the greatest relative value on the use of the woodlands as a habitat for wild plants and animals (14%) and to provide landscape beauty (12%). A second set of interviews, focussed on the recreational use of the woodlands, showed that the main purpose for visiting the woods was walking (median frequency of once a month and duration of between 31-60 minutes). Fifteen out of 88 respondents indicated that they were willing to contribute to support the woods. Many of those not in favour felt such support was a government responsibility. Overall, owners, local residents, government and local conservation groups showed similar relative valuations of the different functions and uses of community woodlands, indicating that there was substantial scope for working together. The research showed that it was useful to apply the ecosystem functions framework to community woodlands. It provided a structure for analysing planting objectives and it encouraged a focus on indirect uses. Stakeholders recognised potential negative functions of the woodland, and it proved useful to include these in the framework. We note the challenges in recognising and placing a high value on the regulation function amongst the range of stakeholders. The framework also helped to identify synergies and tensions between stakeholders without the need for monetising values.